Analytical and numerical study of double-panel confined masonry walls. (July 2021) - Belghiat, Choayb; Plassiard, Jean-Patrick; Messabhia, Ali; Plé, Olivier; Guenfoud, Mohamed
Abstract: Masonry is a traditional construction method in Algeria. It is commonly used in the construction of walls, such as bearing walls or infill panels between columns and beams. Several factors make it difficult to take the material into account in structural analysis, especially in seismic cases. Therefore, engineers usually consider the masonry panel as a nonstructural element. However, the contribution of the masonry panel on the behavior of a building cannot be ignored, particularly, when talking about confined masonry walls. For this reason, a great deal of research has been conducted to generate a database that allows for masonry walls to be considered in the structural analysis. The present paper aims to contribute numerically and analytically to the study of the behavior of double-panel confined masonry walls. Thus, some of the most used analytical models are used to predict the strength and the stiffness of those structures. Moreover, a numerical micro model has been selected from the literature and validated using original experimental tests. Furthermore, one of the most used simplification strategies was adopted. The paper concluded with suggesting some analytical models and with proving the effectiveness of the numerical adopted model to simulate the behavior of confined masonry walls under Pushover tests and finally, the paper recommends future seismic study. Highlights: An original numerical work on one of the mostly used building systems in Algeria. The numerical model studied belongs to the simplified micro modelling approach. Different connections of wall/frames are simulated. The correlation images technique is used in the analysis of results.